2017
DOI: 10.1093/eurpub/ckx059
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and mortality risk of smoking: evidence from the English Longitudinal Study of Ageing (ELSA)

Abstract: Background -It is not clear whether the harm associated with smoking differs by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Of the five NCD-related modifiable risk factors, physical inactivity and current smoking were most strongly associated with subsequent mortality in both cohorts. This agrees with findings from similar studies in other ageing cohorts in the UK, Brazil and elsewhere 8,11,19,35,36 . Worldwide, physical inactivity and smoking are among the major NCD-related risk factors, considered preventable diseases 1 .…”
Section: Discussionsupporting
confidence: 93%
“…Of the five NCD-related modifiable risk factors, physical inactivity and current smoking were most strongly associated with subsequent mortality in both cohorts. This agrees with findings from similar studies in other ageing cohorts in the UK, Brazil and elsewhere 8,11,19,35,36 . Worldwide, physical inactivity and smoking are among the major NCD-related risk factors, considered preventable diseases 1 .…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the results from a Danish study, which found that university graduates and people with ⩾10 years of education presented lower rates of disease compared to those with <10 years of education [51]. In particular, a significant interplay seems to exist between COPD and socioeconomic status [52][53][54][55][56][57]. A significant negative correlation between lung function ( primarily forced expiratory volume in 1 s and forced vital capacity) and socioeconomic status has been established [54].…”
Section: Socioeconomic Status and Copdsupporting
confidence: 86%
“…A relationship exists even after adjusting for smoking status, occupational exposure and race [54]. Smoking is associated with a greater absolute mortality risk due to lung cancer or COPD for individuals in lower socioeconomic groups [55][56][57][58]. Income is inversely associated with COPD treatment initiation [57].…”
Section: Socioeconomic Status and Copdmentioning
confidence: 99%
“…Linking data from death registers with survey and other individual-level data is commonplace in many countries. This practice has enabled a number of prospective cohort studies collecting rich individual-level data, such as the English Longitudinal Study on Ageing (ELSA) and the Health and Retirement Study (HRS), to examine associations between mortality and a wide range of factors (for example see: Lewer et al , 2017 ; Wu et al , 2016 ). The Republic of Ireland has lacked an equivalent data infrastructure and analyses of Irish mortality have therefore been largely limited to unlinked Census data ( Layte & Banks, 2016 ).…”
Section: Introductionmentioning
confidence: 99%